Online learning model development using google classroom on the topic of administration server - Yunita Dwi Andini; Muchlas Muchlas; Jumintono Jumintono (Journal of Vocational Education Studies, 2019)
This study aims to: (1) generate e-learning-based practice learning model of Server Administration which is valid, useful, exciting, and can be applied to improve the learning outcomes of students in the subject of Administration Server; (2) determine the effectiveness of the implementation of Google Classroom on practice learning Administration Server; (3) monitor the learners in the learning process Server Administration practices inside and outside learning. This study is a Research and Development (R & D) to the conceptual model and using research procedures Borg and Gall. Results obtained eligibility percentage of media experts of 77.5% and 78.5% matter experts with criteria are eligible. Implementation level learning model captured very well at 91.66%. The level of attractiveness of the learners XII TKJ 1 amounted to 83.9% and XII TKJ 2 of 85.1% with very interesting criteria. The results of the analysis of the primary field trials assessing the effectiveness aspect, the value of the students after using the learning model and the overall increase learners or 100% to reach KKM with a limit value of 75, so it can be said to be a beneficial learning model to increase the number of learners.